Reading Descartes Consciousness, Body, and Reasoning - Strazzoni, Andrea; Sgarbi, Marco (Knowledge and its Histories, 2023)
This volume takes cue from the idea that the thought of no philosopher can be understood without considering it as the result of a lively dialogue with other thinkers. On this ground, it addresses the ways in which René Descartes's philosophy evolved and was progressively understood by intellectuals from different contexts and eras, either by considering direct interlocutors of Descartes such as Isaac Beeckman and Elisabeth of Bohemia, thinkers who developed upon his ideas and on particular topics as Nicolas Malebranche or Thomas Willis, those who adapted his overall methodology in developing new systems of knowledge as Johannes Clauberg and Pierre-Sylvain Régis, and contemporary thinkers from continental and analytic traditions like Emanuele Severino and Peter Strawson.